Dispersion of marketing activities in business-to-business firms. Issue 6 (1st July 2019) - Blachetta, Marie; Kleinaltenkamp, Michael
Abstract : Purpose: The purpose of this paper is to explore the manifestations and the effects of the dispersion of marketing activities (DoMA) in business-to-business (B2B) firms. Design/methodology/approach: To analyze the manifestations and effects of DoMA, an empirical study was conducted in German B2B firms that consisted of a qualitative pre-study and an online questionnaire-based quantitative study. Findings: Findings highlight that there is not "one" DoMA in B2B firms but that the degrees of dispersion differ with respect to various marketing activities. Moreover, a cluster analysis of the firms with respect to the manifestation of their DoMA reveals interesting differences with respect to the relationship between DoMA and the perceived performance of the marketing activities. Originality/value: This explorative study is one of the first to empirically investigate the extent of DoMA in B2B firms. It shows how different DoMA can be in practice with respect to single marketing activities, as well as firms, and how this impacts the perceived performance of marketing activities.